2011
DOI: 10.1007/s13233-011-0915-8
|View full text |Cite
|
Sign up to set email alerts
|

Compositional effect on the properties of sulfonated and nonsulfonated polymer blend membranes for direct methanol fuel cell

Abstract: Various morphologies of blend membranes were prepared by changing drying condition and composition and their effect on the proton conductivity and the methanol crossover were discussed for direct methanol fuel cell. To obtain high proton conductivity but low fuel loss, highly sulfonated poly(arylene ether sulfone) (IEC=1.9 meq/g for sPAES55, synthesized with 55 mol% sulfonated monomer) was blended with nonsulfonated poly(ether sulfone) (IEC=0 meq/g for RH2000 ® , provided from Solvay) in solution blending mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The entirely hydrophobic polyethylene matrix may be also responsible for the delay of methanol permeation to some extent since the water repelling region in the membrane will not allow methanol to go through. Many researchers reported that methanol permeability and proton conductivity are proportional to IEC of PEMs [ 20 , 21 , 26 , 27 ]. In this case, the PE-g-s-PAES PEMs follows the same general trend.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The entirely hydrophobic polyethylene matrix may be also responsible for the delay of methanol permeation to some extent since the water repelling region in the membrane will not allow methanol to go through. Many researchers reported that methanol permeability and proton conductivity are proportional to IEC of PEMs [ 20 , 21 , 26 , 27 ]. In this case, the PE-g-s-PAES PEMs follows the same general trend.…”
Section: Resultsmentioning
confidence: 99%
“…Some research efforts have been made to prepare Nafion composite membranes with various inorganic materials [ 15 , 16 ]. On the other hand, many alternative polymers, including poly(arylene ether sulfone), poly(etherketone), polyimides [ 17 ], polybenzimidazole (PBI) [ 18 ], and polymer blends [ 19 , 20 , 21 , 22 ], have been studied for direct methanol fuel cells with some limited success. In these aromatic polymers, the hydroxyl (HO•) and hydroperoxyl radical (HOO•) originally formed at the anode can attack double bonds in aromatic rings, causing a ring opening or chain scission [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Howeve, it also exhibits several shortfalls that hinder its large-scale, commercial adaptation, including high cost, limited processibility, poor selectivity (methanol crossover), reduced conductivity at high temperature and low humidity conditions. As an alternative to Nafion, several sulfonated poly(arylene)-based engineering plastics, such as poly(arylene ether sulfone), poly(etherketone), and poly(etheretherketone), were extensively studied for PEMs in the past two decades (7,(9)(10)(11)(12). These polymers offer several advantages of easy processing, good thermal stability and lower manufacturing costs.…”
Section: Introductionmentioning
confidence: 99%
“…However, Nafion also exhibits many shortfalls that hinder its large-scale, commercial adaptation, including high cost, limited processability, poor selectivity (methanol crossover), and reduced conductivity at high temperature and under low humidity conditions. As an alternative to Nafion, several sulfonated poly(arylene)-based engineering plastics, such as poly(arylene ether sulfone), poly(ether ketone), and poly(ether ether ketone), were extensively studied for PEMs in the past 2 decades. , These polymers offer many advantages due to ease of synthesis and fabrication, good thermal stability, high ion exchange capacity, and lower manufacturing costs. Because of the polycondensation mechanism, the synthesis requires high purity monomers with a precise functional group stoichiometry to obtain high molecular weight poly(arylene) polymers.…”
Section: Introductionmentioning
confidence: 99%